The Maternal Risk Factors for Preterm Birth in Universitas Airlangga Hospital Surabaya in 2017-2018 - Almira Maharani; Aditiawarman Aditiawarman; Widati Fatmaningrum (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Preterm birth becomes a global problem due to its high rate of morbidity and mortality. In 2010, it is estimated approximately 15 premature birth cases per 100 lives birth in Indonesia. This study aimed to analyze the maternal risk factors towards preterm birth at Universitas Airlangga Hospital Surabaya in 2017-2018.Methods: This was observational analytic study using case-control approach to observe 178 medical records at Universitas Airlangga Hospital Surabaya. The population of this study was women who had preterm and aterm birth. The sample consisted of case group and control group which were convenient to exclusion and inclusion criteria. Univariate analysis was used to observe the relationship between dependent and independent variable. The significance value was p ≤ 0.05. The data were analysed using SPSS.Results: The research samples consisted of 89 case groups and 89 control groups. The case sample characteristic showed that 36% patients had overweight BMI; 62.9% patients had normal/hypotension; 69.7% patients gave birth to male baby; and 82% patients had no history of disease.There was no patient who used drugs and substance abuse (0%). Mothers aged 20 years old and older than 35 years old had OR = 2.13 (95% CI : 1.106-4.11) to become preterm birth. The primiparous women had risk for preterm birth 2.978 folds (95%, CI : 576-5.625) higher.Conclusion: There was a relationship between maternal age and parity to preterm birth. There was no relationship between maternal education, maternal occupation, hemoglobin levels, history of obstetric complications, and multiple pregnancy to preterm birth.